UPDATE REVIEW OF PHYSALIS: ETHNOGRAPHY VALUE AND ITS USEFULNESS IN STROKE ISCHEMIC DISEASE - Feda Makkiyah (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2023)
One Indonesian herbal medicine that deserves attention is Physalis minimal Linn. Identifying medications and their use in the correct dosages is crucial for effective treatment. Country gooseberry, or Physalis minima Linn, has anti-cancer, anti-diabetic, analgesic, antipyretic, and anti-inflammatory properties. This paper aims to reveal the potential use of Physalis minima Linn in stroke ischemic disease, a substantial current health issue in Indonesia. We used Scopus and Google databases to screen the intended articles with keywords used are TITLE-ABS- KEY (stroke) AND physalis AND antioxidant OR antiinflammation,